2006
DOI: 10.1073/pnas.0604635103
|View full text |Cite
|
Sign up to set email alerts
|

Overdominant quantitative trait loci for yield and fitness in tomato

Abstract: Heterosis, or hybrid vigor, is a major genetic force that contributes to world food production. The genetic basis of heterosis is not clear, and the importance of loci with overdominant (ODO) effects is debated. One problem has been the use of whole-genome segregating populations, where interactions often mask the effects of individual loci. To assess the contribution of ODO to heterosis in the absence of epistasis, we carried out quantitative genetic and phenotypic analyses on a population of tomato (Solanum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
245
0
6

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(274 citation statements)
references
References 33 publications
23
245
0
6
Order By: Relevance
“…The genetic and molecular basis of heterosis has eluded a consensus (32). However, recently an exhaustive study of introgression lines of overlapping portions of a wild tomato genome into domesticated tomato has suggested that the heterotic response results from so-called overdominant QTL (33). In other words, heterozygosity for the introgressed segment of the genome produced a response that was superior to homozygous lines of the respective introgressed line or of domesticated tomato itself.…”
Section: Is There An Involvement In Hybrid Vigor?mentioning
confidence: 99%
“…The genetic and molecular basis of heterosis has eluded a consensus (32). However, recently an exhaustive study of introgression lines of overlapping portions of a wild tomato genome into domesticated tomato has suggested that the heterotic response results from so-called overdominant QTL (33). In other words, heterozygosity for the introgressed segment of the genome produced a response that was superior to homozygous lines of the respective introgressed line or of domesticated tomato itself.…”
Section: Is There An Involvement In Hybrid Vigor?mentioning
confidence: 99%
“…Heterosis has been traditionally attributed to new heterozygous combinations with dominant effects created by the hybridization of genetically divergent parents. As heterosis is conditioned by dominant effects, it is expected to be seen more often with fitness-related traits than with traits that respond well to selection (Semel et al, 2006). Despite the importance of this phenomenon for agriculture and research on the subject that dates back more than 100 years (Darwin, 1876;Bruce, 1910;Jones, 1917), our understanding of the genetic basis for the manifestation of heterosis is still incomplete (Lippman and Zamir, 2007;Charlesworth and Willis, 2009;Baranwal et al, 2012;Schnable and Springer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There are a few models, all involving dominant effects, that explain how different genetic constellations of heterozygous loci can improve the performance of a hybrid as compared with its divergent homozygous parents (Xiao et al, 1995;Lippman and Zamir, 2007). Although many studies in plants have favored one model or another Luo et al, 2001;Semel et al, 2006), other studies have indicated that a combination of a few models is needed to explain the genetic basis underlying heterosis (Yao et al, 2012;Guo et al, 2013;Schnable and Springer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been a large number of genetic analyses in plants with results favoring one hypothesis or another (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), genetic composition pertaining to heterotic performance of crop hybrids has not been fully characterized in an experimental population. There has been no assessment about the relative contributions of these genetic components to heterosis in a crop hybrid.…”
Section: Epistasis | Recombinant Inbred Intercrossmentioning
confidence: 99%